Ark shell Scapharca broughtonii hemocyte response against Vibrio anguillarum challenge. Issue 84 (January 2019) - Zhou, Liqing; Zhao, Dan; Wu, Biao; Sun, Xiujun; Liu, Zhihong; Zhao, Feng; Lv, Zhenming; Yang, Aiguo; Zhao, Qing; Zhang, Gaowei; Ma, Chunyan
Abstract: Scapharca broughtonii is one of the most important Arcidae aquaculture species in the Asia-Pacific region. We aimed to investigate the immune responses of hemocytes from ark shell S. broughtonii hemolymph against pathogens. Hemocyte ultrastructure and immunological activity in response to Vibrio anguillarum challenge were observed by scanning and transmission electron microscopy. Before ultrastructure observation, we used the API ZYM semi-quantitative kit to evaluate the levels of hydrolytic enzymes in the plasma and hemocytes following V. anguillarum infection. An enzyme-linked immunosorbent assay kit was used to investigate the variation in the lysozyme activity and hemocytes following bacterial infection. The results showed that hemocytes were the main defense cells against bacterial infection, whereas plasma played a role in the transport and support of hemocytes. It was presumed that an important function of lysozymes and hydrolytic enzymes in lysosomes was for bacterial digestion. Three major types of hemocytes were observed, namely, red blood cells (RBCs), white blood cells (WBCs), and thrombocytes (TCs). Scanning electron microscopy showed that the normal RBCs appeared pie-shaped with 10 μm diameter and 4 μm central thickness, whereas WBCs were spherical in shape with varying sizes, 4–8 μm diameter, and included small lymphocytes. TCs were long, spindle-shaped, and 12–20 μm in length. The cell membrane surface was smooth and even for all cells before pathogen challenge. Under transmission electron microscopy, RBCs displayed a limited ability to devour and digest bacteria adherent to the cell surface following infection. Many hemoglobin particles were observed in the RBC cytoplasm. WBCs were very active against bacterial invasion and showed a strong ability to digest and decompose infected and wrapped V. anguillarum through phagocytosis and lysosome fusion. Digestive vacuoles rapidly became transparent and were thought to contain increasing quantities of pathogen-induced lysozymes. WBCs that devoured pathogenic bacteria were prone to deformation as well as adhesion to each other. TCs were rich in endoplasmic reticulum (ER) content in their cytoplasm and were widely connected in a net-shaped structure. Mitochondria in TCs formed clusters upon invasion of V. anguillarum in the hemolymph. TCs disintegrated to release the ER into the plasma to form a mesh that facilitated clotting. The ability of circulating hemocytes to quickly modify their morphologies and stainability suggests that S. broughtonii is endowed with highly dynamic hemocyte populations capable of coping with environmental changes and rapidly growing pathogens. Highlights: Three types hemocytes in Scapharca broughtonii have different response to Vibrio anguillarum challenge. There were hemoglobin particles in RBC cytoplasm. WBCs digested and decomposed invasion bacteria actively through phagocytosis and lysosome fusion. TCs disintegrated, releasing the ER into the plasma to form a mesh that facilitates clotting.